The Relationship Between Personality Traits and Coping Styles Among First-Time and Recurrent Prisoners in Poland - Leszko, Magdalena; Iwański, Rafał; Jarzębińska, Aneta (Frontiers in Psychology, 2020)
Individuals with certain personality traits employ adaptive coping strategies. Little research, however, has examined coping strategies among incarcerated individuals. A cross-sectional study was conducted among 465 males who served time in five different prisons in Poland. We examined the relationship between the Big Five personality dimensions and coping styles, and the results demonstrated that neuroticism predicts emotion-oriented coping whereas conscientiousness predicts task-oriented coping strategies. A better understanding of the role of personality traits and its relation to coping strategies may allow for more targeted and effective psychological interventions that will, in turn, improve inmates' abilities to cope with stress.